2021
DOI: 10.1088/1361-665x/ac0f45
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multi-bolt head corrosion using linear and nonlinear shapelet-based acousto-ultrasonic methods

Abstract: Among different types of fasteners used in multiple industries, the bolted connection attracts the most attention due to its low costs and ease of operation. However, bolt failures may induce severe catastrophes if not timely detected. One of the most common bolt failures is bolt corrosion (especially at the bolt head), and bolt head corrosion can significantly affect the mechanical performance of the bolted connection and even the entire structure. So far, no relevant investigations have been conducted to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In this case, we employ datasets from different flanges to respectively serve as training and test sets to study the method's robustness and its potential for practical application. As mentioned above, datasets (1,2,3,4) are captured from the flange A and datasets (5,6,7,8) are from the flange B. The trial settings are shown in Table 5, the performances of different methods are illustrated in Figure 11, and the confusion matrices are given in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, we employ datasets from different flanges to respectively serve as training and test sets to study the method's robustness and its potential for practical application. As mentioned above, datasets (1,2,3,4) are captured from the flange A and datasets (5,6,7,8) are from the flange B. The trial settings are shown in Table 5, the performances of different methods are illustrated in Figure 11, and the confusion matrices are given in Figure 12.…”
Section: Resultsmentioning
confidence: 99%
“…However, such connection still suffers from problems, such as bolt looseness, which may be resulting from chemical erosion, mechanical vibration, impact from foreign objects, and improper installation. 3,4 That is, in the pipeline system, bolted connection represents a point of vulnerability and is prone to self-loosening due to uncertainties, which might lead to disastrous consequences, resulting in economic losses. Therefore, it is important to detect the bolt looseness of the subsea flange.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, considering that most signals captured in structural health monitoring (SHM) systems belong to time series, we may expect the potential of the dual-shapelet networks for damage detection in future work, which is more computation-friendly than deep learning based method. 41 Moreover, we may employ and enhance the shapelet-enhanced AE method to characterize other bolt failures, such as corrosion 42,43 and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, with the help of the rapid development and successful applications of time series analysis methods, many signal processing technologies, including filtering [21], correlation analysis [22], fast Fourier transform [23,24], shorttime Fourier transform [25,26], empirical mode decomposition (EMD) [27,28], ensemble EMD [29], variational mode decomposition (VMD) [30] and other methods [31][32][33][34][35][36], are implemented to enhance or extract the feature of the damage from the complex signals in Lamb wave-based SHMs. Moreover, some researches recently indicate that the singularities of the signal are related to some features of the structural damage, and these singularities are usually obtained by singular spectrum analysis (SSA).…”
Section: Introductionmentioning
confidence: 99%